The Problem of Historical Consciousness in The Jörn Rüsen’s Philosophy and Theory of History - Linchenko, A. A. (Izvestiâ Saratovskogo universiteta. Novaâ seriâ. Seriâ Filosofiâ. Psihologiâ. Pedagogika (Online), 2013)
The article is devoted to a comprehensive analysis of J. Rusen’s theory of historical consciousness. It is one of the most widespread theories in modern foreign philosophy and theory of history. It emphasizes that J. Rusen’s studies of the essence, structure, transformation processes and social functions of historical consciousness should be considered in the context of the idea of rehabilitation of the modern in present foreign philosophy and the searches of the synthesis of the achievements of narrative and hermeneutic philosophy of history. The idea of dynamic nature of J. Rusen’s understanding of historical consciousness is justified. It is related to the interpretation of historical consciousness as a person’s ability to orient in time and be a subject of memory culture. The key concepts of J. Rusen’s theory of historical consciousness such as historical experience, interpretation, orientation, narrative competence and historical culture are analyzed and comprehended in the article. It is concluded that there is a need for further development of J. Rusen’s theory in order to clarify the socio-ontological foundations of historical consciousness.